Usability analysis of graphical interfaces of travel websites according to the universal design principles - Nawrot, Maciej; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2024)
The article examines the usability of tourism website interfaces based on universal design principles, focusing on the growing need for accessibility. The hypothesis defines that altering the layout and increasing the contrast of interface elements will improve the speed at which users find and comprehend information. The research methodology includes an analysis of two tourism interfaces. They were tested by study participant using an eye tracker and the LUT survey. The WAVE tool was used to assess accessibility. The results, presented through heat maps, fixation paths, graphs and surveys, demonstrate that component positioning and increased contrast significantly enhance users’ ability to quickly locate elements in the tourism application.